Theoretical evaluation of the inhibition properties of two thiophene derivatives on corrosion of carbon steel in acidic media - Gece, Ender Gökhan (Wiley-V C H Verlag Gmbh, 2013)
The density functional theory at the B3LYP/6-311G++(d,p) basis set level calculations were performed on two thiophene derivatives used as corrosion inhibitors, namely 2-methylthiophene and 2-(aminomethyl)thiophene, to investigate the correlation between its molecular structure and the corresponding inhibition efficiency (IE%). Quantum chemical parameters such as the highest occupied molecular orbital energy (E-HOMO), the lowest unoccupied molecular orbital energy (E-LUMO), energy gap (E), dipole moment (mu), electronegativity (), hardness (), and the fraction of electrons transferred from the inhibitor molecule to the metal surface (N), have been calculated. A good correlation between the theoretical data and the experimental results was found.
Keywords: corrosion inhibitor; quantum chemical calculations; thiophene